The analysis of transitivity process types of text types in the English textbook “Bahasa Inggris Life Today” for 12th grade students - Sepfia, Dona; Ayudhia, Honesty Yonanda (Universitas Negeri Padang, 2025)
Transitivity is a tool for clause analysis that refers to the way meaning is represented in a clause to express who does what to whom,where, when, and how. Transitivity process types analysis allows one to ascertain if the texts clearly represent the desired language properties and process structures. English textbook entitled “Bahasa Inggris Life Today” is currently used for 12th grade students in Indonesia. In the textbook, variety of complex texts such as narrative, analytical, hortatory and discussion contain current issue in reading section activity. This research aims to examine how transitivity process types are realized in more specific and to compare each text types based on process types to find out the differences in proportions between six process types in each text, so that language models of those text can be provided. The researher used a qualitative method and supported by quantitative elements. An analytical checklist as a guide table to determine the types of transitivity processes based on Halliday theory was created as an instrument of this study. The data of this research gained from 362 clauses of four type of texts in the taxtbook through document analysis. The result of this research shows that all of the process types are found in 3 out of 4 text in different types. Overall, in the type of processes, there were found 50% material, 27% relational, 10% mental, 8% verbal, 2% behavioral and existential. Argumentative texts from the textbook do not fully represent the linguistic complexity expected.